IMPLEMENTASI MEDIA PEMBELAJARAN ULAR TANGGA NUMERASI DALAM PROGRAM ASISTENSI MENGAJAR DI SDN 43 CAKRANEGARA - Urfiani, Helma; Hidayati, Putri; Nurlaela; Komala Rohayanita, Fatihatul; Karisa, Hesti; Handika, Ilham (Jurusan Ilmu Pendidikan FKIP Universitas Mataram, 2025)
This study aims to describe the implementation of the question-and-answer and discussion methods, as well as the role of instructional media in encouraging student engagement in the learning process. This research uses a descriptive qualitative approach with data collection techniques including observation, interviews, and documentation. The results show that the question-and-answer and discussion methods can increase student participation when combined with engaging learning media appropriate to the developmental stage of the children. The use of media such as number cards, visual aids, and educational videos helps create a more interactive and enjoyable learning atmosphere. However, challenges such as limited facilities, differences in student abilities, and time constraints remain obstacles. These findings indicate that interactive and contextual learning approaches have the potential to foster more equitable and meaningful student participation.